Single-Center Retrospective Analysis of Breakthrough Allergic-Like Reactions to Gadobutrol. Issue 7 (July 2019) - Walker, Daniel; Chakraborty, Santanu; Schieda, Nicola
Abstract : Objective: The purpose of this study was to assess the rate and severity of breakthrough allergic-like reactions to gadobutrol. Materials and Methods: Under a waiver from our institutional review board, we performed a key word search of our institutional PACS (Picture Archiving and Communication System) database to identify all allergic-like reactions, which occurred in the setting of gadobutrol administration between December 2009 and August 2018, encompassing approximately 25, 000 gadobutrol injections. Patients with an index allergic-like reaction who underwent a subsequent gadobutrol-enhanced magnetic resonance imaging after a standard 13-hour corticosteroid and antihistamine premedication protocol before repeat injection were identified. Patient characteristics, volume of gadobutrol injected, and severity of index and breakthrough reactions were recorded and compared by χ 2 test, t test, and Spearman correlation. Results: The index allergic-like reaction rate to gadobutrol was 0.28% (69/25000). Of the patients who had an index allergic-like reaction, 45% (31/69) had a subsequent magnetic resonance imaging with gadobutrol injection and premedication with a breakthrough reaction rate of 35% (11/31). Most index reactions were mild in severity (91% [63/69]), and most breakthrough reactions were also typically mild (91% [10/11]). One patient escalated from a mild index reaction to a moderate breakthrough reaction despite premedication. There was no correlation between volume of gadobutrol injected (ρ = −0.004, P = 0.98) or association with age ( P = 0.74), although female patients had higher breakthrough reaction rates ( P = 0.007). Conclusions: Allergic-like reactions to gadobutrol are rare; however, breakthrough reactions occur with moderate frequency despite premedication, and although generally of mild severity, in our series, one breakthrough reaction escalated in severity.